Legal Protection for Registered Trademark Owners Against Bad-Faith Trademark Registration: Comparative Study of Law Number 20 of 2016 and Indonesian Ulama Council Fatwa Number 1/MunasVII/MUI/5/2005 - Muhammad Fakhry Jaidan; Annisa Sativa (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
Trademark violations in Indonesia, including counterfeiting, imitation, and unauthorized registration, continue to occur and indicate weaknesses in legal awareness and intellectual property rights enforcement. Such practices cause economic losses to legitimate trademark owners and create unfair business competition. This study aims to analyze the legal protection afforded to registered trademark owners against bad-faith trademark registration and to compare its regulation under Law Number 20 of 2016 concerning Trademarks and Geographical Indications and the Fatwa of the Indonesian Ulema Council Number 1/MUNAS VII/MUI/5/2005 concerning the Protection of Intellectual Property Rights. This research employs a normative legal method using statutory and comparative approaches. The findings reveal that Indonesian positive law provides both preventive and repressive protection through exclusive trademark rights, cancellation mechanisms, compensation claims, and legal sanctions against infringers. Meanwhile, Islamic law recognizes trademarks as a form of property right that must be protected based on the principles of justice, public benefit, and the prohibition of unlawfully appropriating the rights of others. Both legal systems acknowledge the importance of trademark protection, although they differ in their philosophical foundations. The study concludes that positive law and Islamic law complement each other in promoting legal certainty, justice, and fair business practices.